The Effect of the Quality of the Tiktok Shop Information System on Small and Medium Enterprises in Palopo City on the Satisfaction of Generation Z Customers - Fitriana Umar; Yayuk Pratiwi Seran; Nurfadhillah Safrillah; Nuraeni Nuraeni; Hendriawan Patadungan (Jurnal Multidisiplin Sahombu, 2026)
This study aims to determine the effect of information system quality on generation Z customer satisfaction on the use of TikTok Shop by MSMEs in Palopo City. The background of this research is based on the increasing use of digital platforms, especially TikTok Shop, as a transaction medium of interest to the younger generation. The method used in this research is quantitative with a simple linear regression approach, where data is obtained through distributing questionnaires to 123 generation Z respondents who have made transactions through TikTok Shop MSMEs. The results showed that the quality of information systems has a positive and significant effect on customer satisfaction. This is evidenced by the significance value of <0.001 and the t-count value of 9.236> t-table. The coefficient of determination (R Square) value of 0.413 shows that the quality of the information system is able to explain 41.3% of the variation in customer satisfaction, while the remaining 58.7% is influenced by other variables outside the study.